Property Rights for the Poor: Effects of Land Titling - Sebastian Galiani; Ernesto Schargrodsky (Universidad Nacional de La Plata, Centro de Estudios Distributivos, Laborales y Sociales (CEDLAS), 2010)
Secure property rights are considered a key determinant of economic development. The evaluation of the causal effects of property rights, however, is a difficult task as their allocation is typically endogenous. To overcome this identification problem, we exploit a natural experiment in the allocation of land titles. In 1981, squatters occupied a piece of land in a poor suburban area of Buenos Aires. In 1984, a law was passed expropriating the former owners' land to entitle the occupants. Some original owners accepted the government compensation, while others disputed the compensation payment in the slow Argentine courts. These different decisions by the former owners generated an exogenous allocation of property rights across squatters. Using data from two surveys performed in 2003 and 2007, we find that entitled families substantially increased housing investment, reduced household size, and enhanced the education of their children relative to the control group. These effects, however, did not take place through improvements in access to credit. Our results suggest that land titling can be an important tool for poverty reduction, albeit not through the shortcut of credit access, but through the slow channel of increased physical and human capital investment, which should help to reduce poverty in the future generations.
Keywords: P14; Q15; O16; J13; 330; Property rights; land titling; natural experiment; urban poverty; Sachenrecht; Bodenrecht; Städtische Armut; Buenos Aires